Live Birth Following Uterine Transplantation From a Nulliparous Deceased Donor - Fronek, Jiri; Janousek, Libor; Kristek, Jakub; Chlupac, Jaroslav; Pluta, Marek; Novotny, Robert; Maluskova, Jana; Olausson, Michael (Transplantation, 2021)
BACKGROUND: Nulliparous uterine grafts have never been used in uterus transplantation (UTx), possibly due to presumed infertility. Our objective was to verify the feasibility of nulliparous uterine graft transplantation. METHODS: The Czech Uterus Transplant Trial (registered under ClinicalTrials.gov, identifier NCT03277430) is a 2-arm trial comparing the efficacy of deceased donor (DD) versus live-donor uterus transplant (10 patients in both arms). A 25-year-old patient suffering from inborn absolute uterine factor infertility underwent a DD uterus transplant. The donor was a 20-year-old nulliparous brain-dead donor. RESULTS: The transplant procedure was uneventful. The posttransplant period was complicated by (1) recurrent episodes of acute cellular rejection, (2) neutropenia necessitating the administration of granulocyte colony-stimulating factor, (3) vaginal anastomotic stenosis treated with the insertion of a self-expanding stent, (4) the concurrence of Clostridium difficile colitis and acute appendicitis, and (5) temporary renal function impairment of a combined cause. Two years after the UTx, after the fourth embryo transfer, the patient became pregnant. Apart from gestational diabetes mellitus, the pregnancy was uneventful. Due to preterm contractions, delivery was achieved via caesarean section at gestational age 34 + 6 years. The postoperative course was uneventful for both the mother and the newborn. CONCLUSIONS: Herein, we report the first live birth after a DD UTx in Europe. This report provides a proof of concept that nulliparous uteri may present a suitable source of uterine grafts for UTx. Stenting may serve as a feasible treatment method for vaginal anastomotic stenosis.
Keywords: Pregnancy; Infertility, Female; Congenital Abnormalities; Live Birth; dárci tkání; Reproductive Techniques, Assisted; Stents; Mullerian Ducts; Time-to-Pregnancy; Treatment Outcome; Donor Selection; ductus Mülleri; Humans; Tissue Donors; poruchy sexuálního vývoje s karyotypem 46, XX; vrozené vady; stenty; doba do početí; Female; Fertility; ženská infertilita; 46, XX Disorders of Sex Development; ženské pohlaví; Uterus; Parity; mladý dospělý; Adult; Young Adult; výběr dárců; Postoperative Complications; narození živého dítěte; asistovaná reprodukce; uterus; dospělí; lidé; pooperační komplikace; těhotenství; parita; fertilita; výsledek terapie